Implementasi Jaringan Syaraf Tiruan (JST) Untuk Memprediksi Jumlah Penjualan Gas 3Kg Menggunakan Metode Backpropagation - B. Tambunan, Holpan Torang; Hartama, Dedy; Gunawan, Indra (TIN: Terapan Informatika Nusantara, 2021)
In a service company, there are customers who become company consumers. Customer satisfaction is formed from the level of performance and service of the company. One level of customer satisfaction can be measured from the level of gas sales of 3 Kg. Therefore, the 3 kg LPG gas pankalan Pematangsiantar needs to overcome the problem of overcoming the amount of 3 kg gas sales at each LPG base in order to improve their performance and service. So research is needed to predict the amount of gas sales of 3 Kg through the Neural Network method with the backpropagation algorithm to find the best results that will be used to solve the problems faced.